Vocal Techniques for the Instrumentalist - Rosine, Amy (New Prairie Press, 2018)
Vocal Techniques, the course title used at many institutions, is essentially a voice class for instrumentalists, and is a required course for instrumental music education majors seeking all-level certification. Students take at least one Vocal Techniques course to learn proper singing technique along with basic pedagogy and can include teaching techniques as they apply to adolescent singers. The focus of the course is the development of the individual singing voice. This includes breathing, tone production, articulation, musicality and textual expression and understanding. Students also develop confidence in front of groups, improve their general vocal quality, and learn that a healthy voice serves them well in the general and performance classroom. The purpose of this text is to teach instrumental music education students about vocal production as it applies to solo singing. Beginning with a foundational understanding of breathing, singers will learn about the vocal instrument (anatomy), how to create clear, pleasant, tone (phonation and resonance), pronounce words clearly (articulation and diction) and how singing is similar, and different, from playing an external instrument. This is the first textbook to explore teaching voice as it directly pertains to playing an instrument.